Esmolol vs. nitroglycerin: attenuating hemodynamic response to laryngoscopy and intubation - Held, Cassie (International Journal of Advanced Nursing Studies, 2016)
Hemodynamic response to laryngoscopy and intubation is a common occurrence with the potential for harmful effects. Many drugs have been utilized throughout the years to attenuate this response with mixed results. This review compares the efficacy of two drugs, esmolol and nitroglycerin, in attenuating hemodynamic response to laryngoscopy and intubation. A systematic review was performed compiling all previous studies detailing the efficacy of esmolol in comparison to nitroglycerin for this purpose. Esmolol was found to consistently attenuate hemodynamic responses of blood pressure and heart rate with greater efficacy than nitroglycerin, and is thus recommended over nitroglycerin for use in this role.